1997
DOI: 10.1093/gerona/52a.5.m264
|View full text |Cite
|
Sign up to set email alerts
|

Methodology and Feasibility of a Home-Based Examination in Disabled Older Women: The Women's Health and Aging Study

Abstract: Extensive, research-oriented physical evaluation can be successfully and safely performed in a home setting. In future studies, home-based examination may be preferable, as participation in the WHAS examination substantially exceeded rates for clinic-based exams in similar populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 19 publications
0
85
0
1
Order By: Relevance
“…Test-retest reliability for 4MGS is better than that reported over an 8-foot course [19] and as reliable as over 6 m [20]. A 4-m course has also been shown to be feasible in 90% of households [21], allowing the possibility of using the 4MGS as a tool in communityor home-based studies. Consistent with this, in our study, we observed very high ICCs for both test-retest and interobserver reliability.…”
Section: Discussionmentioning
confidence: 84%
“…Test-retest reliability for 4MGS is better than that reported over an 8-foot course [19] and as reliable as over 6 m [20]. A 4-m course has also been shown to be feasible in 90% of households [21], allowing the possibility of using the 4MGS as a tool in communityor home-based studies. Consistent with this, in our study, we observed very high ICCs for both test-retest and interobserver reliability.…”
Section: Discussionmentioning
confidence: 84%
“…This site was chosen because it is the region of the lower leg with the largest circumference of the calf with very little variability across individuals. 25 Different tissues in the analyses were separated according to different density thresholds, using the ''soft tissue'' algorithm. On the basis of the calibration, AT, muscle, and cortical bone were measured with mineral equivalent densities of 0, 80, and 1,200 mg/cm 3 , respectively.…”
Section: Pqct Measuresmentioning
confidence: 99%
“…The three tests were administered after a standardized protocol as previously described (10). Using the results of the three performance tests, a summary performance score was calculated.…”
Section: Measures Of Physical Functionmentioning
confidence: 99%